Blood pressure measurement by oscillometric and auscultatory methods in normotensive pregnant women - Estefanie Siqueira Vigato; José Luiz Tatagiba Lamas (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to compare blood pressure values obtained by auscultatory and oscillometric methods in different gestational periods, considering cuff width. Method: it is a cross-sectional and quasi-experimental study approved by the Research Ethics Committee. The sample consisted of 108 low-risk pregnant women. Blood pressure measurements were performed in gestational periods of 10-14, 19-22 and 27-30 weeks. Results: The oscillometric device presented values similar to the auscultatory method in systolic blood pressure, but overestimated diastolic blood pressure. Underestimation of blood pressure occurred when using the standard width cuff rather than the correct width cuff in both measuring methods. Conclusion: Verification of brachial circumference and use of adequate cuffs in both methods are indispensable to obtain reliable blood pressure values in pregnant women. We recommend performance of additional studies to evaluate diastolic blood pressure overestimation by the Microlife 3BTO-A.